2000
DOI: 10.2307/3246590
|View full text |Cite
|
Sign up to set email alerts
|

Spatial pattern of Quercus ilex and Quercus pubescens recruitment in Pinus halepensis dominated woodlands

Abstract: Abstract. European Mediterranean landscapes have undergone changes in structure in recent years as a result of widespread agricultural land abandonment and cessation of silvicultural regimes. Studies concerning the regeneration dynamics of dominant forest species have become critical to the prediction of future landscape trends in these changing forest stands. Quercus ilex (holm oak) and Q. pubescens (downy oak) are considered to be the terminal point of secondary succession in extensive areas of the Mediterr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
65
3
2

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 92 publications
(74 citation statements)
references
References 36 publications
4
65
3
2
Order By: Relevance
“…These findings and differences in seedling abundance (Table 1) suggest that currently dominant Pinus nigra forests could be replaced by more mixed pine-oak stands at lower altitude sites, whereas it would probably persist as the sole or dominant species at higher altitudes. A replacement of pine by oak would agree both with previous studies conducted in Mediterranean pine forests (Lookingbill & Zavala, 2000) and with the observed higher shade tolerance of Quercus compared with pine seedlings (Figure 3). However, successional change is likely to depend on the silvicultural treatments applied and on acorn dispersal.…”
Section: Patterns Of Tree Regenerationsupporting
confidence: 92%
“…These findings and differences in seedling abundance (Table 1) suggest that currently dominant Pinus nigra forests could be replaced by more mixed pine-oak stands at lower altitude sites, whereas it would probably persist as the sole or dominant species at higher altitudes. A replacement of pine by oak would agree both with previous studies conducted in Mediterranean pine forests (Lookingbill & Zavala, 2000) and with the observed higher shade tolerance of Quercus compared with pine seedlings (Figure 3). However, successional change is likely to depend on the silvicultural treatments applied and on acorn dispersal.…”
Section: Patterns Of Tree Regenerationsupporting
confidence: 92%
“…Some of the processes (e.g., competition for light and selfthinning), which underlie gap dynamics in temperate forest ecosystems, may differ under a Mediterranean climate, since soil moisture can be a decisive factor in addition to light availability. In fact, many studies have reported that vertical growth of Mediterranean tree species is not controlled by apical dominance, as is common in temperate forests (Vilà and Sardans, 1999), because shade tolerance is not the main regulator of forest succession under Mediterranean conditions (Benayas, 1998;Lookingbill and Zavala, 2000). All this suggests that increasing seasonality and summer drought, as predicted by climate-change models for temperate-boreal regions of Europe, will have profound consequences on the stand structure and gap dynamics of forest ecosystems, including Abies spp.…”
Section: Introductionmentioning
confidence: 99%
“…As holm oak is a late succession species and seedling recruitment benefits from canopy shade of mature tress and early successional species (Lookingbill and Zavala, 2000), it is frequently cultivated under a half shade. This practice is considered to produce higher quality seedlings because it presumably reduces foliar damage caused by the heat load and high irradiation that occurs during the summer.…”
Section: Introductionmentioning
confidence: 99%